Chasing the ghost of fracking in the Vaca Muerta Formation: Induced seismicity in the Neuquén Basin, Argentina - Ryan Schultz; Guillermo Tamburini-Beliveau; Sebastián Correa-Otto; Javier Grosso-Heredia (Seismica)
Earthquakes are known to be induced by a variety of anthropogenic causes, such as hydraulic fracturing.  In the Neuquén Basin of Argentina, hydraulic fracturing has been used to produce hydrocarbons trapped in the shales of the Vaca Muerta Formation.  Correspondingly, incidences of seismicity there have increased.  We collect information on well stimulations and earthquakes to perform statistical analysis linking these two datasets together.  Spatiotemporal association filters suggest that the catalogue of events is biased towards hydraulic fracturing operations.  After accounting for false-positives, we estimate that ~0.5% of operations are associated with earthquakes.  These associated event-operation pairs show highly correlated temporal signals (>99.99% confidence) between seismicity/injection rates.  Based on this evidence, we argue that many of these earthquakes are induced.  We support this argument by comparing the geological setting of the Neuquén Basin against conditions needed for fault reactivation in other susceptible/seismogenic basins. This recognition adds to the growing list of (hydraulic fracturing) induced seismicity.